Oxygen‐Initiated and Regulated Controlled Radical Polymerization under Ambient Conditions. (4th July 2018) - Lv, Chunna; He, Congze; Pan, Xiangcheng
Abstract: A rapid oxygen‐initiated and ‐regulated controlled radical polymerization was conducted under ambient temperature and atmosphere. The reaction between triethylborane and oxygen provides ethyl radicals, which initiate and mediate the radical polymerization. The controlled radical polymerization was achieved using RAFT chain transfer agents (CTA) without any process of removing oxygen, providing well‐defined polymers with almost full conversion (>95 %) in a short period (15 min). High‐throughput screening was used to discover the suitable conditions for various CTA and monomers. To show the versatility of this method, a polymer library containing 25 well‐defined polymers with different compositions (block and statistical copolymers) and molecular weights were synthesized in 1 h via high‐throughput synthesis technique. A polymer‐painting technique was developed using this method, forming films with spatial control and excellent control in molecular weight and dispersity.